Reference Brain and Blood Concentrations of Olanzapine in Postmortem Cases. Issue 9 (14th June 2018) - Nedahl, Michael; Johansen, Sys; Linnet, Kristian
Abstract: The antipsychotic drug olanzapine may be subject to postmortem redistribution. This complicates the toxicological evaluation in postmortem cases and a supplementary analysis of brain tissue may be an advantage. We report reference brain and blood concentrations of olanzapine from 40 forensic autopsy cases. Each case was assigned to one of three groups according to the cause of death: (A) fatal intoxication by olanzapine alone; (B) fatal intoxication by olanzapine in combination with other drugs and (C) olanzapine was not related to the cause of death. Quantification of olanzapine in brain and blood was performed by ultra-performance liquid chromatography with tandem mass spectrometry using a validated method. A linear correlation between concentrations in blood and brain from 40 cases was found with a correlation coefficient of 0.87. The median brain:blood ratio was 2.5 (10–90%: 1.2–5.8, range: 0.72–10.4). For the A cases ( n = 2), the concentrations in brain (Br) and femoral blood (FB) were: Br: 2.1–3.6 mg/kg, FB: 0.99–1.2 mg/kg; for the B cases ( n = 17) the 10–90% were: Br: 0.27–1.0 mg/kg (range: 0.13–1.3 mg/kg) FB: 0.11–0.57 mg/kg (range: 0.096–0.65 mg/kg) and the 10–90% of the C cases ( n = 21): Br: 0.05–0.49 mg/kg (range: 0.040–0.87 mg/kg) FB: 0.02–0.14 mg/kg (range: 0.008–0.15 mg/kg). These results can serve as reference concentrations for the interpretation of postmortem forensic cases.